Effect of cosmos caudatus kunth leaves on the lipid profile of a hyperlipidemia-induced animal model - Perumal, Vikneswari; A. Hamid, Azizah; Ismail, Amin; Saari, Khozirah; Abas, Faridah; Ismail, Intan S.; Maulidiani,; Lajis, Nordin. H.; Khatib, Alfi (ESci Journals Publishing, 2014)
Hyperlipidemia, a metabolic disorder closely associated with the modern life-style and eating habits, is increasingly prevalent among the world population. This study was conducted on obese rats to evaluate the efficacy of Cosmos caudatus leaves as a treatment of hyperlipidemia. Hyperlipidemic conditions were induced in rats by submitting them to a high-fat diet during 3 months. After this, the rats were administered 200 mg/kg body weight of an ethanolic C. caudatus leaf extract or 35 mg/kg body weight atorvastatin for four weeks. The rats treated with the C. caudatus extract showed a significant (P<0.05) reduction of plasma triglycerides, total cholesterol, low density lipoprotein-cholesterol and glucose, and a significant (P< 0.05) increase in high density lipoprotein-cholesterol and Atherogenic Index values. The study indicated that supplementation with C. caudatus has a potential for the treatment of hyperlipidemia.